The Role of E-Module Application Media as Health Literacy to Increase Knowledge of Cadres in the Prevention and Management of Diarrhea in Children: Improving Cadre Competence through E-Modul Aplication Health Education to Reduce Children Diarrhea Cases - Islaeli Islaeli; Sartini Risky; Asbath Said (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Diarrhea is still a major global problem and the biggest cause of death in children under five in Indonesia. Cadres have an important role in improving children's health so it is necessary to increase knowledge about the prevention and handling of diarrhea in children. E-module application media is one of the health literacy options that can provide experience accessing the process. Objectives: to analyze the effect of e-module application media in the prevention and treatment of diarrhea in children Methods: Pre-experiment with one group without control pretest and post-test design was used. The population in this study was 30 posyandu cadres in Punggolaka Village using total sampling. The instrument used e-module application media to provide education on preventing and managing diarrhea in children and questionnaires to measure cadre knowledge. Results: The results showed an increase after the post-test with a mean value of 63.00 before intervention and 85.30 after intervention, while the paired t-test showed a significant effect with a p-value of <0.001 (<0.005). Conclusions: There is a significant effect of education through the e-module application media on the knowledge of posyandu cadres in Punggolaka Village